Urbanization, loneliness and mental health model - A cross-sectional network analysis with a representative sample - Dominika Ochnik; Bartłomiej Buława; Paulina Nagel; Marek Gachowski; Marcin Budziński (Scientific Reports)
Abstract With increasing urbanization, more people are exposed to mental health risk factors stemming from the urban social or physical environment. However, research on the relationship between urbanization and mental health is lacking. This cross-sectional study aimed to explore the relationships of the physical environment (spatial cohesion and urban environment) and social factors (neighborhood cohesion) with mental health (stress, anxiety and depression symptoms) and physical health and the mediating role of loneliness based on the proposed theoretical model. The study was conducted in Metropolis GZM (Silesia, Poland) in a representative sample of 3296 residents (48% women). The measurements used were the PSS-10, GAD-7, PHQ-9, R-UCLA3 and neighborhood cohesion scale. ANOVA results showed that city residents had better mental health indices than residents of villages and small towns. The network approach revealed that urbanization was one of the most influential nodes and played the role of a bridge between all other nodes. The model was confirmed and showed that the relationships between the physical environment and mental health were consecutively mediated by neighborhood cohesion and loneliness. Spatial cohesion related to factors of the physical environment and physical health, while physical health was directly connected to sociodemographic factors and weakly to stress. Anxiety was the strongest risk factor. Mental health can be improved by social and architectural factors, such as strengthening neighborhood cohesion and improving neglected buildings.